Periosteal fenestration vestibuloplasty procedure for sulcus deepening in a hemimandibulectomy patient following implant therapy - Bhavna Jha Kukreja; Udayan Gupta; Vidya Dodwad; Pankaj Kukreja (Wolters Kluwer Medknow Publications, 2014)
Ablative surgery of the jaws may be necessary when malignant disease or destructive benign disease occurs. Surgical reconstruction needs to include the restoration of masticatory function so that the quality of life after the operation is optimal. When resection includes part of the upper or lower jaw, the aim of reconstruction should encompass not only the restoration of aesthetics, speech and swallowing, but also the recreation of an alveolar ridge suitable for prosthetic rehabilitation of the dental occlusion. In the present case, depth of vestibule was inadequate following implant placement thereby severely compromising prosthetic rehabilitation. Hence vestibuloplasty was done with periosteal fenestration operation, which provided retention and stability of mandibular prosthesis and hence greatly improved his overall quality of life.